CONSTRAINTS TO SMALLHOLDER CREDIT FARM INVESTMENT: A CASE STUDY OF COFFEE FARMING IN MAJOGE CHACHE LOCATION, (KISII DISTRICT) - Ombuki, Charles (My University, 1995)
This study analyses the constraints to smallholder credit farm investment. The data for the study were collected in Majoge Chache Location, Kisii District. A total of 40 respondents were , interviewed for a period extending from 17th of July to the 5th of August, 1995. A list of farmers in Majoge Chache Location who had borrowed funds for investment in coffee farms was obtained from the Loans Officer based at Ogembo Divisional Headquarters. Following the list, systematic sampling procedure was then applied in which every sixth loanee farmer was picked until a sample size of 40 was obtained. The estimated results of both semi-log and double log models indicate that initial household endowment of housing services and investment in the farm activities have very significant effects on credit farm investment. Specifically, sample farmers with quality houses were observed to invest more of the credit they received on the farm. The main non-farm activity to which most of the sample farmers diverted farm credit was school fees. The results indicated that other variables studied do not have significant effects on the proportion of credit invested in coffee farms in the study area. These variables are: Family size. number of children in school, price of coffee per kg., and household income